Generational cohort differences in psychological ownership: How does Gen Z come to feel ownership in an intangible world? - Gröschel, Andrea; P. Kirk, Colleen; F. Martinez, Luis; Brandão, Amélia; Torres-Pruñonosa, José (European Journal of Management and Business Economics, 2026)
Purpose This paper aims to examine the theoretical foundations of psychological ownership (PO) across generational cohorts, with a specific focus on Generation Z (Gen Z). Design/methodology/approach A conceptual framework was developed through an extensive review and synthesis of the PO literature. Findings The study identifies three core motivational drivers, identity expression, control and security, as distinctive antecedents of PO among Gen Z. Building on these drivers, the research proposes that Gen Z is more likely than previous cohorts to experience stronger ownership feelings toward experiential and intangible products. These insights are consolidated into a conceptual framework that extends PO theory by integrating a generational perspective and linking it to emerging forms of digital and access-based consumption. Originality/value To the best of the authors’ knowledge, this research is among the first to conceptualise PO through a generational lens. It offers a comprehensive framework that advances theoretical understanding of how Gen Z develops PO in an increasingly dematerialised and experiential consumption landscape.
Keywords: psychological ownership; generation Z; consumer behaviour; experiential consumption; digital goods; identity expression; generational differences; access-based consumption; intangible assets; conceptual framework; digital consumption; consumer identity